Pendampingan Pengembangan Kreativitas UMKM Melalui Inovasi Produk Oatmeal Madu pada UMKM Body Scrub - Aditya Indra S; Aldo Brilianta; Windi Dian Pertiwi; Heny Hartono (Universitas Katolik Soegijapranata, 2019)
This community service aimed to develop UMKM (Micro, Small, Medium Enterprises) creativity through product innovation in the form of honey oatmeal body scrub at UMKM at Sambiroto, Semarang.The era of globalization that has been followed by technological advancement and business competition must bepositively responded with a breakthrough in the creativity of UMKM entrepreneurs. Creativity can produce innovations that can advance micro, small and medium enterprises (UMKM). Accompaniment to UMKM through the innovation of honey oatmeal body scrub products can prove the importance of UMKM to be more creative in order to produce high quality product innovations that can be more widely marketed